Effects of nonnative species on the stability of riverine fish communities. Issue 8 (9th May 2020) - Erős, Tibor; Comte, Lise; Filipe, Ana Filipa; Ruhi, Albert; Tedesco, Pablo A.; Brose, Ulrich; Fortin, Marie‐Josée; Giam, Xingli; Irving, Katie; Jacquet, Claire; Larsen, Stefano; Sharma, Sapna; et al.
Abstract : Despite the increasing ubiquity of biological invasions worldwide, little is known about the scale‐dependent effects of nonnative species on real‐world ecological dynamics. Here, using an extensive time series dataset of riverine fish communities across different biogeographic regions of the world, we assessed the effects of nonnative species on the temporal variability and synchrony in abundance at different organizational levels (population, metapopulation, community and metacommunity) and spatial scales (stream reach and river basin). At the reach scale, we found that populations of nonnative species were more variable over time than native species, and that this effect scaled up to the community level – significantly destabilizing the dynamics of riverine fish communities. Nonnative species not only contributed to reduced community stability, but also increased variability of native populations. By contrast, we found no effect of nonnative species dominance on local interspecific synchrony among native species. At the basin scale, nonnative metapopulations were again more variable than the native ones. However, neither native metapopulations nor metacommunities showed differences in temporal variability or synchrony as nonnative species dominance increased basin‐wide. This suggests a 'dilution effect' where the contribution to regional stability of local native populations from sites displaying low levels of invasion reduced the destabilizing effects of nonnative species. Overall, our results indicate that accounting for the destabilizing effect of nonnative species is critical to understanding native species persistence and community stability.